Kritik Sosial dan Politik dalam Kumpulan Puisi "Potret Pembangunan dalam Puisi” Karya W.S. Rendra - Adi Nurhadi (Indonesian Journal of Applied Linguistics Review, 2017)
The purpose of this study is to examine (1) the social critiques contained in a collection of poems "The Portrait of development in the Poetry" by W.S. Rendra, (2) the existing political criticism in the poetry collection of "The Portrait of Development in Poetry" Work W.S. Rendra, (3) causes of their social criticism in the collection of poems "The Portrait of Development in Poetry" Work W.S. Rendra, and (4) The cause of their political critiques in the collection of poems "The Portrait of Development in the Poetry" by W.S. Rendra. The method used was a qualitative method of sociological literary review, based on the results f the analysis; it revealed that there was an element in the analysis of social and political critiques. Namely, there were 24 poems from 26 poems, each of 14 poems about the 10 social and political critiques. Meanwhile, in analyzing social critiques, I obtained three main aspects: (1) a critique of social justice, (2) critiques of the government’s economy and (3) critiques of human rights. Furthermore, in analyzing political critiques, I found there were three main aspects, which consisted of (1) critiques of the government, (2) a critique of power, and (3) critiques of the institution. While the cause of social critiques that is made up of social inequality and social injustice. And the latter is the cause of political critiques, namely power. This is exactly what the focus of the author to find social and political critiques in this study